The brazilian tourist on international trips: A behavioral analysis - Pereira, Manuel Sousa (2023)
Tourism is an activity heavily dependent on the movement of people and travel (with different motivations). As a result, tourism has been heavily affected by the COVID-19 pandemic since the beginning of 2020. The number of trips has dropped considerably across the world and particularly in Brazil. Several studies show that one of the biggest dreams of Brazilians is to travel, but only about 1% of the inhabitants in the country usually travel internationally annually. Despite being a tiny amount of the population, it is more than 2 million people who travel and consume in the international tourism sector. This study proposes to analyze the behavior of Brazilian tourists on trips abroad, describing through a survey the choices of these travelers. From an interdisciplinary perspective, this manuscript presents inputs for marketing, (i.e., consumer behavior), for tourism (i.e., management of tourism services) and for management.